Wip1 Deficiency Promotes Neutrophil Recruitment to the Infection Site and Improves Sepsis Outcome - Shen, Xiao-Fei; Zhao, Yang; Cao, Ke; Guan, Wen-Xian; Li, Xue; Zhang, Qian; Zhao, Yong; Ding, Yi-Tao; Du, Jun-Feng (Frontiers in Immunology, 2017)
Sepsis is defined as an uncontrolled host response to infection, and no specific therapy or drugs have been used in clinical trials currently. Discovering new therapeutic targets for sepsis treatment has always been a central problem in the field of sepsis research. Neutrophils stand at the first line in controlling infection, and have been identified to be dysregulated with impaired migration and antimicrobial function during sepsis. Based on our previous results on demonstrating wild-type p53-induced phosphatase 1 in controlling neutrophil development, we explored the possible relationship among Wip1, neutrophils and sepsis in the present study. Wip1-deficient mice exhibited improved outcomes in CLP-induced sepsis model with enhanced bacterial clearance and less multi-organ damage. The protection seen in Wip1 KO mice was mainly due to an increased accumulation of neutrophils in the primary infectious locus mediated by the decreased internalization of CXCR2, as well as by an increased antimicrobial function. Additionally, we also identified a negative correlation between CXCR2 and Wip1 in human neutrophils during sepsis. Pharmacological inhibition of Wip1 with its inhibitor can also prevent the internalization of CXCR2 on human neutrophils treated with lipopolysaccharides in vitro, and significantly improve the outcome in CLP-induced sepsis model. Taken together, our results demonstrate Wip1 can negatively regulate neutrophil migration and antimicrobial immunity during sepsis, and inhibition of Wip1 can be a potential therapeutic target for sepsis treatment.